The Investigation of Reactions of Atomic Metal Anions with Small Hydrocarbons and Alcohols in the Gas Phase - Halvachizadeh, Jaleh (Université d'Ottawa / University of Ottawa, 2014)
Hydrocarbons are an abundant resource of carbon and hydrogen. For example, fossil can be used to produce useful organic compounds. However hydrocarbons seem to be inert. Thus, the activation of the C-H bond is a popular research area. Metals play the main role in most catalysts that convert hydrocarbons to starting materials in industry. The study of metals is important because the properties of the metal core greatly influences the reactivity of a catalyst.1 The study of the chemistry of metals in the gas phase provides valuable information about the properties of metals. This information can be expanded to the chemistry of metals in the condensed phase. Furthermore, it is often both more accurate and more manageable to study the profile of a reaction in the gas phase than in the condensed phase.2,3 There are many studies about metal cations in the gas phase due to ease of their production. However metals have low electronegativity, limiting the study of gas phase metal anions. Recently, a simple and efficient method to generate atomic metal anions was developed at the University of Ottawa in Dr. Mayer's research laboratory.4-6 Atomic metal anions of Fe-, Co-, Cu-, Ag-, Cs- and K- were generated in an electrospray ionization (ESI) source of a mass spectrometer (MS). In this thesis study generated metal anions were reacted with small hydrocarbons of pentane, 1-pentene, 2-pentene and 1-pentyne to investigate the role of different metal anions in the activation of the C-H bond. Also metal anions were reacted with small alcohols of 1-butanol, 2-butanol and 2-methyl-2-propanol to compare the results. Metal anions showed a variety of reactions with these hydrocarbons and alcohols. Fe- was the only metal anion to show the electron transfer reaction, indicating that alcohols are more electronegative than Fe- and less electronegative than other metal anions. Fe-, Co- and Ag- showed the complex formation reaction. All metal anions showed the deprotonation reaction. A deprotonation reaction follows the harpoon mechanism, the long range proton abstraction7, and depends on the gas phase acidity of fragments. The most informative reaction observed was the dehydrogenation reaction because a metal-containing fragment is observed as a product in the spectrum of this reaction. The observation of a metal-containing fragment in the spectrum is significant because it emphasizes the important role that metal anions play in this reaction. This suggests that a dehydrogenation reaction involves metal insertion into a C-H bond. Among the transition metal anions, it was observed that Fe- and Cu- are more reactive than Co- and Ag- with regards to the dehydrogenation reaction, probably because Fe- and Cu- have a greater hydrogen affinity than Co- and Ag- that facilitates the hydrogen abstraction reaction. Another reason could be that Fe- and Cu- have a greater gas phase acidity that leads to a more stable intermediate in the course of the reaction. The results of this thesis study revealed that Cs- and K- could not abstract H from these substrates, probably due to the absence of occupied d orbitals that would facilitate insertion into a C-H bond. Some metal anions not only can insert into a C-H bond of alcohols but also can insert into a C-O bond of alcohols to form metal hydroxide anions. Alcohols are more reactive than hydrocarbons with regards to reactions with metal anions because they contain a functional group. This thesis study shows that some atomic metal anions are able to activate the C-H bond and abstract two hydrogens to form a double bond in hydrocarbons. It is probable that the electronic configuration, gas phase acidity and hydrogen affinity of the metal anions governs their reactivity.
Keywords: Metal anions; Mass spectrometry; Metal dihydride anion; Metal hydride anion; Metal hydroxide anion; Metal insertion mechanism; Activation of C-H bond; Bisdehydrogenation; Collision cell; CID; Dehydrogenation; Deprotonation; ESI; Enthalpy; Gas phase; Gas phase acidity; Generation of atomic metal anions in the gas phase; Dissociation of deprotonated alcohol; Hydrogen affinity; Oxygen contamination in gas phase experiments; Reactions in gas phase; Reactions of hydrocarbons and alcohols with metal anions; Reactions of metal anions; Spontaneous dissociation in gas phase; Triple quadrupole